Interpretation of Potential Fields and Detection of Deep Faults of Kut-Dewania- Fajir Area, Central Iraq - AL-Banna, Ahmed S.; Daim, Falih, M.; AL-Zubaidi, Ali .A.M. (Iraqi Journal of Science, 2021)
Gravity and magnetic data are used to study the tectonic situation of Kut- Dewania- Fajir and surrounding areas in central Iraq. The study includes the using of window method with different spacing to separate the residual from regional anomalies of gravity and magnetic data. The Total Horizontal Derivative (THD) techniques used to identify the fault trends in the basement and sedimentary rocks depending upon gravity and magnetic data. The obtained faults trends from gravity data are (N30W), (N60W) (N80E) and (N20E) and from magnetic data are (N30W), (N70E), (N20E),(N10W),(N40E). It is believed that these faults extend from the basement to the lower layers of the sedimentary rocks except the N60W trend that observed clearly in gravity interpretation. It is believed that this trend may be related to sedimentary cover only. Most residual gravity and magnetic anomalies coincide with each other concerning location and extension, which indicate that they may be created from common sources. There is a large positive gravity anomaly located at east of Hai-Fajir cities coincide with the relatively negative residual RTP magnetic anomaly. It is believed that this anomaly may represent an uplift structure within the sedimentary cover lying over deep basement rock.